Pengaruh Labelisasi Halal, E-Marketplace, dan Gratis Ongkos Kirim terhadap Keputusan Pembelian Produk - Muhammad Zaini El Wahyu; Yoyo Hambali; Aditia Yuski Fahlevi (STEBI Global Mulia Cikarang, 2025)
This study aims to determine the effect of halal labeling, e-marketplace and free shipping on purchasing decisions for Go-Milku SR12 milk at the Qasrina Store, Sekumpul Complex, Bukit Pinang Village, Samarinda Ulu District, Samarinda City. This type of research is quantitative research conducted in April - May 2025. The sample used was 80 respondents from the Sekumpul Complex, Samarinda City with a purposive sampling technique. Data collection was carried out by distributing questionnaires online (google form). Data analysis in this study used the IMB SPSS 30 software application. The results of the study found that: (1) Halal labeling has a positive and significant influence on purchasing decisions. (2) Free shipping has a positive and significant influence on purchasing decisions. However (3) E-marketplaces do not show any influence which is positive and significant towards purchasing decisions. Further research is suggested to explore other variables and expand the scope of the area to see whether similar results apply outside the Sekumpul Complex, Bukit Pinang Village, Samarinda Ulu District, Samarinda City.